The Effect Of Nurses’ Caring Services On The Anxiety Level Of Patients Before Surgery At Rskd Duren Sawit In 2025 - Doni Ramdoni; Cusmarsih Cusmarsih (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Preoperative anxiety is a common psychological response experienced by patients before surgery, characterized by feelings of worry, fear, and tension. High anxiety levels can adversely affect hemodynamic stability, increase oxygen demand, prolong recovery time, and increase the risk of intraoperative complications. Caring services provided by nurses play a crucial role in reducing preoperative anxiety through therapeutic communication, emotional support, and comprehensive patient education. Research Objective: To determine the relationship between nurse caring services and anxiety levels of preoperative patients. Research Method: This study used a cross-sectional analytical design. The sample consisted of 94 preoperative patients at the Central Surgery Installation of Duren Sawit Regional General Hospital, East Jakarta, in November-December 2025. The sampling technique used was consecutive sampling. Data were collected using the Swanson Caring questionnaire and Hamilton Anxiety Rating Scale (HARS). Univariate and bivariate analyses were conducted using Spearman Rank correlation test. Research Results: All respondents (100%) rated nurse caring services in the good/optimal category (mean score 9.87). The majority of respondents experienced mild anxiety (64.9%), moderate anxiety (33.0%), and severe anxiety (2.1%) with a mean HARS score of 19.53. There was no significant relationship between nurse caring services and preoperative anxiety levels (p-value 0.098, r=0.172). However, there was a significant difference in anxiety levels between male and female patients (p-value 0.025), with females having higher anxiety levels. Conclusions and Recommendations: Although no significant statistical relationship was found between nurse caring services and preoperative anxiety levels, caring services remain clinically important in creating a therapeutic environment. Female patients require more intensive interventions to manage preoperative anxiety. Future research should use longitudinal designs and more sensitive instruments to measure caring variations.